2021
DOI: 10.1177/00220345211004498
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba gingivalis Exerts Severe Pathogenic Effects on the Oral Mucosa

Abstract: The protozoan Entamoeba gingivalis colonizes the healthy oral mucosa with a prevalence of 15%. Colonization can be asymptomatic, and it is considered not pathogenic. However, it is able to invade lacerated oral mucosa, where it ingests fragments of live cells, suggesting pathogenous potential. Here, we characterized the transcriptomes of gingival cells after infection with E. gingivalis using RNA sequencing and observed pathogen interaction with the epithelial monolayer barrier by scanning electron microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…In the present study, the levels of cytokines in GCF were expressed as the total amount per 30s of sampling time, as previously described (Ye et al, 2020;Arvikar et al, 2021). Previous in vitro studies showed that the expression of the neutrophil chemokine IL8 gene, as well as that of IL1b and TNF, was significantly increased in E. gingivalis-infected gingival epithelial cells (Bao et al, 2020;Bao et al, 2021). Similar results were revealed from our GCF data.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the levels of cytokines in GCF were expressed as the total amount per 30s of sampling time, as previously described (Ye et al, 2020;Arvikar et al, 2021). Previous in vitro studies showed that the expression of the neutrophil chemokine IL8 gene, as well as that of IL1b and TNF, was significantly increased in E. gingivalis-infected gingival epithelial cells (Bao et al, 2020;Bao et al, 2021). Similar results were revealed from our GCF data.…”
Section: Discussionsupporting
confidence: 86%
“…Once attached to the gingival epithelial cells, E. gingivalis could form long cylindrical structures which termed digipodia, extending into the cytoplasma. Through the digipodia, E. gingivalis might secrete material into the target cell or ingest material from the target cell (Bao et al, 2021). Besides direct destruction and invasion in periodontal tissues, the immune response and subgingival microbial dysbiosis induced by E. gingivalis could also be its potential pathogenic mechanism in periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that the human oral protist E. gingivalis is the host of redondoviruses explains their statistical association to periodontitis, since E. gingivalis is also strongly linked to gum disease, possibly causally ( Bao et al. 2020 , 2021 ; Badri et al. 2021 ).…”
Section: Discussionmentioning
confidence: 73%
“…Similarly to infection of colon epithelium with E.h ., infection of oral epithelial cells with E.g . causes significant induction of proinflammatory cytokine signaling cascades, leading to >1500 fold increased expression of interleukin-8 [9], [7, 10], which is the major cytokine for attraction and activation of neutrophils in inflammatory regions.…”
Section: Introductionmentioning
confidence: 99%